Dimensi Adat dan Dinamika Komunitas Dayak di Kalimantan Timur - Semiarto Aji Purwanto; Haryono Haryono (Antropologi Indonesia, 2019)
Adat is Indonesian concept for customary law, a living law practiced by people in their communities. For decades after independence of Indonesia in 1945, the role of adat was gradually changed and replaced by national legal laws. It, however, did not really abolish the existence of adat in daily practices of particular communities. Since the 1998 Reformation, adat has been becoming a central academic and policy discussions as the changing of political system in Indonesia introduces regional autonomy policy in the regency level. Adat, since then, is extensively used to various activisms and practices. For examples, the indigenous people movement employs the term ‘masyarakat adat’ to replace ‘indigenous people’; and as it appears in some regencies, adat is used as the basis for developing new local regulations. Our findings in Kutai Kartanegara, East Kalimantan, indicated that adat is used to represent at least five ideas with different meaning and degree of obedience. Adat in our discussion refer to traditional inventions in a community, re-creation of the old Kutai Sultanate regulations, local regulations issued by local governments, agreements between parties when an event occurs, and strategies developed by activists to dealing with power. Although they are contesting and competing in everyday life, we argue that it was aimed mainly for the sake of practicality rather than for ideological reasons.